Pricing Real Assets with Costly Search - Williams, Joseph T. (Review of Financial Studies, 1995)
Markets for many real assets are characterized by sequential search followed by bilateral bargaining between matched buyers and sellers. For a category of real assets, the joint, intertemporal valuation problems of buyers, owners, and sellers, and the associated Nash pricing function are solved explicitly. In equilibrium, the average transaction price is a noisy, proportional random walk, and the liquidity premium is positive for matched owners. Depending on the values of the parameters, the liquidity premium can be substantial. In a related problem of optimal development with costly search, the optimal exercise point, cost of development, and value of the undeveloped asset are calculated analytically. With search, development can occur sooner and undeveloped assets have lower market values than the standard solution without search.